C5aR1 Activation Drives Early IFN-γ Production to Control Experimental Toxoplasma gondii Infection - Briukhovetska, Daria; Ohm, Birte; Mey, Fabian T.; Aliberti, Julio; Kleingarn, Marie; Huber-Lang, Markus; Karsten, Christian M.; Köhl, Jörg (Frontiers in Immunology, 2020)
Toxoplasma gondii (T. gondii) is a parasite infecting animals and humans. In intermediate hosts, such as humans or rodents, rapidly replicating tachyzoites drive vigorous innate and adaptive immune responses resulting in bradyzoites that survive within tissue cysts. Activation of the innate immune system is critical during the early phase of infection to limit pathogen growth and to instruct parasite-specific adaptive immunity. In rodents, dendritic cells (DCs) sense T. gondii through TLR11/12, leading to IL-12 production, which activates NK cells to produce IFN-γ as an essential mechanism for early parasite control. Further, C3 can bind to T. gondii resulting in limited complement activation. Here, we determined the role of C5a/C5aR1 axis activation for the early innate immune response in a mouse model of peritoneal T. gondii infection. We found that C5ar1-/- animals suffered from significantly higher weight loss, disease severity, mortality, and parasite burden in the brain than wild type control animals. Severe infection in C5ar1-/- mice was associated with diminished serum concentrations of IL-12, IL-27, and IFN-γ. Importantly, the serum levels of pro-inflammatory cytokines, including IL-1α, IL-6, and TNF-α, as well as several CXC and CC chemokines, were decreased in comparison to wt animals, whereas anti-inflammatory IL-10 was elevated. The defect in IFN-γ production was associated with diminished Ifng mRNA expression in the spleen and the brain, reduced frequency of IFN-γ+ NK cells in the spleen, and decreased Nos2 expression in the brain of C5ar1-/- mice. Mechanistically, DCs from the spleen of C5ar1-/- mice produced significantly less IL-12 in response to soluble tachyzoite antigen (STAg) stimulation in vivo and in vitro. Our findings suggest a model in which the C5a/C5aR1 axis promotes IL-12 induction in splenic DCs that is critical for IFN-γ production from NK cells and subsequent iNOS expression in the brain as a critical mechanism to control acute T. gondii infection.